Case report: Management of recurrent pupillary optic capture with sutureless surgical technique using 7–0 polypropylene flange - Kim, Dong Hyeon; Moon, Da Ru Chi; Kang, Yong Koo; Park, Dong Ho; Shin, Jae Pil; Kim, Dai Woo; Do, Jae Rock (Frontiers in Medicine, 2024)
To report a novel surgical technique for recurrent pupillary optic capture after flanged intraocular lens (IOL) fixation METHODS: In this retrospective case series, we detail our use of two parallel 7-0 polypropylene sutures passed between the iris plane and the optic of scleral-fixated IOL to address pupillary optic capture. Flanges were created using ophthalmic cautery to secure it to the sclera without suture.Two eyes with pupillary optic capture underwent a sutureless surgical technique using 7-0 polypropylene flanges. No recurrences of pupillary optic capture were observed during the 1-year follow-up.Our sutureless surgical technique using a 7-0 polypropylene flange was an effective, efficient, and less invasive approach for treating recurrent pupillary optic capture.